ORGANISASI KEMASYARAKATAN ISLAM DALAM MEWUJUDKAN CHECK AND BALANCES TERHADAP KEBIJAKAN PEMERINTAH: Perspektif Undang-Undang Organisasi Masyarakat - Pratama, Rihan (al-Rasῑkh: Jurnal Hukum Islam, 2023)
The task of the opposition in government is to provide oversight of government policies and behavior. The opposition party, which in a democracy functions as a control over the incumbent (Check and Balances), has shifted in favor of power. As a result, NGOs, labor unions, and community organizations are practically without a solid opposition. This research is a type of library research, with primary law in the form of the Law on Community Organizations used as a source for study, and also secondary sources in the form of books, journals, and so on. Community Organizations (Ormas) are basically concerned with maintaining the unity, integrity, and interests of the nation. CSOs are established with the aim of protecting, maintaining, and strengthening the unity of the Nation. This is in line with Law 17/2013, which mandates that mass organizations become a bridge for the voice of the people. Although this has been done, it is still ineffective, because the government has turned a deaf ear to it.